Sweatshop : the history of an American idea - Hapke, Laura (Rutgers University Press, 2004)
Arguing that the sweatshop is as American as apple pie, Laura Hapke surveys over a century and a half of the language, verbal and pictorial, in which the sweatshop has been imagined and its stories told. Not seeking a formal definition of the sort that policymakers are concerned with, nor intending to provide a strict historical chronology, this unique book shows, rather, how the "real" sweatshop has become intertwined with the "invented" sweatshop of our national imagination, and how this mixture of rhetoric and myth has endowed American sweatshops with rich a.